Evaluation of the influence of chamomile vaginal gel on dyspareunia and sexual satisfaction in postmenopausal women: A randomized, double-blind, controlled clinical trial - Zahra Bosak; Mina Iravani; Eskandar Moghimipour; Mohammad Hossein Haghighi zadeh; Parivash Jelodarian; Mohammad Reza Khazdair (Mashhad University of Medical Sciences, 2020)
Objective: The purpose of this study was to determine the effect of chamomile vaginal gel on dyspareunia and sexual satisfaction in postmenopausal women. The phytoestrogenic properties of Matricaria chamomilla were the reason for selection of this plant. Materials and Methods: This double-blind clinical trial research was conducted on 96 eligible postmenopausal women referring to Gotvand city Health Center No. 1 in 2018. In this research, 96 postmenopausal women complaining from dyspareunia and sexual dissatisfaction were randomly assigned into three groups (each contained 32 subjects) to receive 5% chamomile vaginal gel, conjugated estrogen vaginal cream and placebo gel, for 12 weeks. All women completed the Larsson and a four-degree pain self-assessment questionnaires. Data was analyzed using SPSS version 22. A p-value of less than 0.05 was considered significant. Results: After the intervention period, a significant difference was seen between the intervention and the placebo group in the mean sexual satisfaction (p<0.001). Also, a significant reduction was seen in painful sexual intercourse between the groups using vaginal gel of chamomile and conjugated estrogen vaginal cream (95% CI: chamomile: 0.68-1.04, estrogen: 0.63-0.98, placebo: 1.8-2.1; p<0.001).  Conclusion: Using chamomile vaginal gel can cause a reduction in painful sexual intercourse and an increase in sexual satisfaction in postmenopausal women.